Kontribusi Produk Olahan Nanas Terhadap Pendapatan pada Usaha Oleh-Oleh Khas Prabumulih Toko Kue Darrel - Meirani Betriana; Chairani Adelina (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The Contribution of Pineapple Processed Products to Revenue in the Typical Souvenir Business of Prabumulih Darrel Cake Shop" In the midst of globalization and increasingly advanced and strict trade flows, local wisdom plays an important role in maintaining the cultural identity of a region and supporting local economic growth. One of the tangible forms of local wisdom is local processed products that not only represent the cultural wealth of an area but also have the potential to increase business income. This study aims to find out the contribution of processed pineapple products as local wisdom in increasing income in the Prabumulih souvenir business. This type of research is descriptive using quantitative data. The data source used was secondary data obtained from interviews about processed pineapple products and income obtained by Darrel Cake Shop. The population in this study is data on various processed products and income with samples taken are the types of processed products sold and the revenue of Darrel cake shops in 2021-2023 . The data analysis techniques used in this study include data reduction interpreted as summarizing activities, selecting main things that are adjusted to the focus of the research, in this case choosing the types of processed pineapple and non-processed pineapple products obtained through observation, interviews, and documentation that are focused on the formulation of problems in the research. After the data is reduced, it will provide a clearer picture to researchers so that it can be described and compiled systematically so that it is easier to understand, especially in analyzing the contribution of processed pineapple products in increasing business income. The last stage, namely drawing conclusions, is the stage where the researcher draws conclusions from the data findings. After all the data has been described and compiled systematically, conclusions are drawn and the results of the research are validated.